Spatial structure of standing wave electromagnetic fields at the lower harmonics of the ionospheric Alfvén resonator - Prikner, K. (Karel); Feygin, F. Z.; Raita, T. (Studia Geophysica et Geodaetica, 2014)
During the multiband wave Pc1 event on March 7, 2001 the EISCAT UHF and VHF incoherent scatter radars operated simultaneously covering an exceptionally wide altitude range of the ionosphere similar to 90-2000 km. This made possible to test the ionospheric Alfven resonator (JAR) model over a large altitude range. The three lowest JAR eigenfrequencies, where the most of the Pc1 pulsation signal bands occur, were selected for the spatial analysis of the standing wave electromagnetic fields, applying the full-wave numerical simulation method. The altitude spread of amplitude maxima and nodes together with polarization characteristics of oscillation maxima in the horizontal plane are presented The comparison of the standing wave oscillations on the altitude profile with the signal amplitude observed on the ground is also presented.